Gellan gum spongy‐like hydrogel‐based dual antibiotic therapy for infected diabetic wounds - Ana Isabel Mendes; Alexandra Gabriel Fraga; Maria João Peixoto; Ivo Aroso; Adhemar Longatto‐Filho; Alexandra Pinto Marques; Jorge Pedrosa (Wiley, 2023)
Abstract Diabetic foot infection (DFI) is an important cause of morbidity and mortality. Antibiotics are fundamental for treating DFI, although bacterial biofilm formation and associated pathophysiology can reduce their effectiveness. Additionally, antibiotics are often associated with adverse reactions. Hence, improved antibiotic therapies are required for safer and effective DFI management. On this regard, drug delivery systems (DDSs) constitute a promising strategy. We propose a gellan gum (GG)‐based spongy‐like hydrogel as a topical and controlled DDS of vancomycin and clindamycin, for an improved dual antibiotic therapy against methicillin‐resistant Staphylococcus aureus (MRSA) in DFI. The developed DDS presents suitable features for topical application, while promoting the controlled release of both antibiotics, resulting in a significant reduction of in vitro antibiotic‐associated cytotoxicity without compromising antibacterial activity. The therapeutic potential of this DDS was further corroborated in vivo, in a diabetic mouse model of MRSA‐infected wounds. A single DDS administration allowed a significant bacterial burden reduction in a short period of time, without exacerbating host inflammatory response. Taken together, these results suggest that the proposed DDS represents a promising strategy for the topical treatment of DFI, potentially overcoming limitations associated with systemic antibiotic administration and minimizing the frequency of administration.